PENGARUH PENGGUNAAN MEDIA SOSIAL TERHADAP KEPUTUSAN PENDAFTARAN MAHASISWA DI STMIK SURYA INTAN KOTABUMI - Bangsawan, Laksamana; Rohmah, Aida (STMIK Pringsewu, 2024)
Social media has become the main platform for the younger generation to get information and communicate. In this digital era, it is important to understand the influence of social media on students' enrollment decisions in higher education. This study aims to Analyze the influence of social media usage on students' enrollment decisions at STMIK Surya Intan. Find out the types of social media that have the most influence on students' enrollment decisions. Formulate strategies for utilizing social media to increase the number of applicants at STMIK Surya Intan. This research method uses a quantitative method with a survey research design. The research sample was prospective students who registered at STMIK Surya Intan in the 2024/2025 academic year. Data were collected through an online questionnaire. The results of the study on the influence of social media usage on students' enrollment decisions. Information about the types of social media that have the most influence on students' enrollment decisions. Strategies for utilizing social media to increase the number of applicants at STMIK Surya Intan. The results of the analysis show that the frequency of Instagram use has a significant positive correlation (r = 0.75, p 0.01) with the decision to register. In addition, multiple linear regression analysis showed that both the frequency of Instagram use and the influence of friends' recommendations significantly predicted the decision to enroll (R² = 0.56, p 0.01). This finding indicates the important role of social media, especially Instagram, in the student decision-making process.